Exploring school principals' leadership practices of serving the learners - Jeremiah Khoarane (S&Co Publishing, 2024)
There is an emerging interest in applying servant leadership theory in leading the school. Little is known about school principals' practices of Servant leadership to learners. The purpose of this paper is to explore school principals’ practices of servant leadership focusing on learners. The information is derived from a large project focused on the practices of servant leadership among school principals. This paper is situated within the interpretive paradigm and employs a qualitative approach to comprehend the leadership practices of school principals in serving learners. Data was generated through interviews with school principals and teachers from two Lesotho high schools. We held individual face-to-face interviews with each of the two principals. One focus group of teachers was interviews from each school. Each focus group was made up of eight teachers. The two school principals were interviewed individually The Findings suggest that school principals served learners in various ways. Findings indicate that learners were served through motivation, cherishing of self-efficacy, development of child friendly school environment, and enhancing high academic performance. We argue that servant leadership necessitates a paradigm shift in the relationship between formal leaders, such as the principal, and learners. School principals must prioritize learners, placing them at the center, where they become more important than the principal as a leader.